PENGEMBANGAN MODUL PRAKTIKUM KALKULUS INTEGRAL BERBASIS APLIKASI WXMAXIMA TERHADAP PEMAHAMAN KONSEP MATEMATIS - Dafrita, Ivan Eldes; Nurmaningsih, Nurmaningsih (Universitas Tanjungpura, 2019)
This study aims to determine whether there is difference and influence of Integral Calculus practical activity based on WxMaxima application on students concept comprehension ability. This research uses experimental method, with posttest only control design. Research data in the form of ability test comprehension concept of math given after practicum activity given during 8 times meeting. The data of the research were analyzed using the t-test to see whether there was a difference, and effect size to see the magnitude of influence. The result of the research shows that: (1) there is a difference of concept comprehension ability among students who follow Integral Calculus based on WxMaxima application with those who do not follow lab; (2) there is influence of the use of Integral Calculus practical module based on WxMaxima application to students' concept comprehension ability and magnitude of influence is high category.